ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM SURAT RESMI PADA BIDANG SINTAKSIS SISWA KELAS KELAS VIII MTs N LUBUK BUAYA KOTA PADANG - Afif Rofii (Jurnal Ilmiah Dikdaya, 2017)
Abstract: The Purpose of this research is to describe: (1) Indonesian language errors of class VIII D students in MTsN Lubuk Buaya City of  Padang in writing official letters through syntax perspective; and (2) the level of students capability in writing official letters through some aspects, such as; spelling, diction, and sentence structure. To gain those purposes, analysis should be done. Furthermore, students’ language errors in writing official letters should be categorized.  The result of the research shows that (1) Indonesian language errors of class VIII D students in MTsN Lubuk Buaya Cityof Padang in writing official letters in syntax point of view covers spelling, diction, and sentence structure; and (2) the level of students capability in writing official letters is very low. There are only 25,83% of the students (7 students) who master spelling, there are 31,67 % of the students (9 students) who master in diction, and 40% of the students (12 students) who master sentence structure. Keywords: Language Errors, Official Letters and Syntax